Report on a heronry at the Rajshahi University Campus (Journal of Life and Earth Science, 2011)
Key words: Heronry; cormorant; heron; egret; RU campus DOI: 10.3329/jles.v5i0.7358 J. Life Earth Sci., Vol. 5: 97-100, 2010